Characteristics of Male Sex Men Who Screen for Sexually Transmitted Infections in an Effort to Prevent HIV/AIDS - Pratidina, Eki; Maulana, Imam (Research Collaboration Community (Rescollacom), 2023)
HIV/AIDS is an infectious disease that is currently happening in Indonesian society. Globally, the number of HIV (Human Immunodeficiency Virus) has tended to increase from 2010-2019 with the spread of the virus in all age groups. The high number of HIV cases in Indonesia is due to free-sex behavior and the low level of public knowledge about risky sexual behavior, prevention of unwanted pregnancies, and sexually transmitted diseases. The total number of people with HIV/AIDS (ODHA) in Indonesia as a whole until March 2021 was recorded at 427,201 people, and AIDS cases were 131,417 people. Data from the Ministry of Health of the Republic of Indonesia, the number of people living with HIV based on risk factors found that 27.2% of homosexuals were 26.3% of the male sex men and 0.9% of drag. One of the high-risk groups is male sex men who have abnormal sexual deviations and have a tendency to lead to sexual crimes. This study aims to obtain an overview of the characteristics of male sex men who carry out screening for Sexually Transmitted Infections to prevent HIV/AIDS. This research method uses a quantitative description method. The population is male sex men as many as 85 people. The sampling technique used purposive sampling, obtained a sample of 46 male sex men. Data collection techniques with questionnaires. Data analysis using univariate analysis. The results showed that the age of the majority (63%) of the respondents was between 21-30 years old, the domicile of the majority (65.2%) of the respondents resided in Bandung, the last education of the majority (56.5%) of the respondents had a senior high school education, almost all respondents (76.1%) as many as 35 people had jobs, history of screening Sexually Transmitted Infections negative and the activity of using condoms during sex, the majority (71.7%) of respondents always use condoms during sex. Productive age is an age that needs to get special attention, especially in risky sexual activity, this can be seen from the use of condoms when male sex men have sexual intercourse. This becomes our joint consideration in efforts to prevent HIV/AIDS in productive age. This study aims to obtain the results of risky sexual behavior in male sex men through screening for Sexually Transmitted Infections to prevent HIV/AIDS